Immunoinformatic based identification of cytotoxic T lymphocyte epitopes from the Indian isolate of SARS-CoV-2 - Viswajit Mulpuru (Nature Portfolio, 2021)
Abstract The Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has turned into a pandemic with about thirty million confirmed cases worldwide as of September 2020. Being an airborne infection, it can be catastrophic to populous countries like India. This study sets to identify potential cytotoxic T lymphocyte (CTL) epitopes in the SARS-CoV-2 Indian isolate which can act as an effective vaccine epitope candidate for the majority of the Indian population. The immunogenicity and the foreignness of the epitopes towards the human body have to be studied to further confirm their candidacy. The top-scoring epitopes were subjected to molecular docking studies to study their interactions with the corresponding human leukocyte antigen (HLA) system. The CTL epitopes were observed to bind at the peptide-binding groove of the corresponding HLA system, indicating their potency as an epitope candidate. The candidacy was further analyzed using sequence conservation studies and molecular dynamics simulation. The identified epitopes can be subjected to further studies for the development of the SARS-CoV-2 vaccine.